The Efforts of Principals in Bengkulu To Ensure The Effectiveness of Post-Pandemic Educational Supervision - Rustiyono, Rustioyono; April Yanti, Fitri; Danim, Sudarwan; Badeni, Badeni; Putra, Syailendra; Arma Yenni, Yuli; Purwaningsih, Sri (Sekolah Tinggi Agama Islam Al Hidayah, 2023)
This study aims to characterize the actual circumstances surrounding the oversight that school principals performed during the epidemic. Even though learning takes place at home, teachers still need to maintain administrative discipline and follow any applicable requirements when implementing the program. This study uses a qualitative methodology and is a field investigation. Snowball sampling was utilized to gather information, while interviews and observations with principals, teachers, parents, and students at senior high schools in Bengkulu City were employed as data gathering strategies. Data reduction, data presentation, and data verification were the methods employed in data analysis. The study's findings outline 14 features that the principal of the school should have in place to ensure that instructional monitoring is effective throughout the epidemic.